Etherology, or, The philosophy of mesmerism and phrenology : including a new philosophy of sleep and of consciousness : with a review of the pretensions of neurology and phreno-magnetism / by J. Stanley Grimes. - Grimes, J. Stanley (James Stanley), 1807-1903. (Tufts University. Tisch Library., 2015)
1 online resource (350 pages) : illustrations.; Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.